2018
DOI: 10.21776/ub.jfmr.2018.002.02.6
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of anchovy length size using puring net in Pulolampes Waters, Brebes Regency of Central Java

Abstract: Ikan Teri (Stolephorus sp.) merupakan komoditas bernilai ekonomi di Pulolampes-Brebes umumnya ditangkap dengan jaring puring yang berbahan utama waring. Distribusi ukuran ikan teri berguna untuk mengetahui sebaran ukuran ikan teri dan informasi tentang stok, serta sebagai data dasar upaya pengelolaan dan pemanfaatan ikan teri. Penelitian ini bertujuan menganalisa komposisi ikan hasil tangkapan untuk mendapatkan keragaan struktur hasil tangkapan dan ukuran serta pola pertumbuhan ikan teri hasil tangkapan jaring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Conversely, autumn and winter exhibit a significant prevalence of smaller-sized anchovies, particularly noticeable during autumn, with sizes ranging from 30 to 50 mm. This suggests recruitment events occurring within the existing population [63,64]. The size dominance observed in each season aligns with Zhu et al [27], who found that larger anchovies were more common in spring, whereas sizes ranging from 20 to 70 mm were dominant in winter.…”
Section: Spatial-temporal Distribution Of Japanese Anchovysupporting
confidence: 87%
“…Conversely, autumn and winter exhibit a significant prevalence of smaller-sized anchovies, particularly noticeable during autumn, with sizes ranging from 30 to 50 mm. This suggests recruitment events occurring within the existing population [63,64]. The size dominance observed in each season aligns with Zhu et al [27], who found that larger anchovies were more common in spring, whereas sizes ranging from 20 to 70 mm were dominant in winter.…”
Section: Spatial-temporal Distribution Of Japanese Anchovysupporting
confidence: 87%
“…With the advancement of technology in the capture fisheries sub-sector, including boats, fishing gear, and deck machinery, a fisherman will most likely consider employing technology that is more ecologically friendly from an economic standpoint. Like the puring net fishermen in Pulolampes, the 'ciker net' in Teluk Penyu, then the 'cantrang' on the north coast of Java [21,22,23], and the BSC fisherman in Rembang, they are basically aware that the use of eco-friendly and economical technology will be very helpful them in carrying out fishing activities, but again problems will always arise, both technical and non-technical which makes them return to old habits that tend to be inefficient and not environmentally friendly. Especially lately, the increase in fuel oil is felt by fishermen so they choose not to go to sea because the results obtained are not proportional to the capital spent.…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of this anchovy fishery research is to classify the forms, parameters of the waters and to estimate the characteristics of the habitat. Research on anchovy fisheries has been performed by previous researchers both domestically and internationally, such as in the waters of the Gulf of Palabuhanratu (Utami et al 2018), the coastal waters of Tegal (Sutono & Susanto 2016), the waters of Pulolampes, Central Java (Sasmita et al 2018), the coastal waters of Spermonde Pangkep (Safruddin et al 2014), the waters of the Gulf of Bone (Safruddin et al 2018). In the waters of the deep Ambon Bay (Ongkers 2008), in the South Andaman waters (Kumar et al 2015), in the waters of the Mediterranean Sea (Giannoulaki et al 2012).…”
Section: Introductionmentioning
confidence: 99%